Analysis of the Causes of Delays in Pilotage and Towing Services within the Integrated Ship Operation Digital System at PT. Pelabuhan Indonesia (Persero) Banjarmasin Branch - Syaifullah, Firman; Kuncowati, Kuncowati; Supangat, Supangat (Universitas Hang Tuah, 2025)
This study examines the causes of delays in pilotage and towing services within the integrated ship operation digital system at PT. Pelabuhan Indonesia (Pelindo) Banjarmasin Branch. Pelindo strives to provide timely and efficient pilotage services for ships docking or entering and exiting the port, while ensuring adequate safety and comfort to minimize the risk of accidents for vessels operating in the Barito River channel and Banjarmasin Port. However, these efforts have not been fully successful due to challenges in improving timely and efficient services. Data analysis reveals that the delays are caused by a combination of external and internal factors, as well as constraints within the integrated ship operation digital system. This research employs qualitative methods including observation, interviews, and documentation. The issues have resulted in decreased operational efficiency, increased accident risks, economic losses, and customer dissatisfaction. Therefore, a comprehensive and integrated strategy is necessary to enhance the performance of pilotage and towing services at Banjarmasin Port.